2018
DOI: 10.3390/ijms19020595
|View full text |Cite
|
Sign up to set email alerts
|

Secreted and Tissue miRNAs as Diagnosis Biomarkers of Malignant Pleural Mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a rare but aggressive tumor that originates in the pleura, is diagnosed in advanced stages and has a poor prognosis. Accurate diagnosis of MPM is often difficult and complex, and the gold standard diagnosis test is based on qualitative analysis of markers in pleural tissue by immunohistochemical staining. Therefore, it is necessary to develop quantitative and non-subjective alternative diagnostic tools. MicroRNAs are non-coding RNAs that regulate essential cellular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 100 publications
2
28
0
Order By: Relevance
“…In lung cancer, neuroendocrine features, which are associated with an aggressive clinical course, were linked with miR‐375, 15 indicating a relationship between histopathology and miR expression. In MM, the expression profile and prognostic and diagnostic significance of miR have been reported; however, the significance of miR was not concordant, most likely due to the variety of approaches, techniques and collected samples 16,17 . In this study, we identified high expression of miR‐199/214 in SM with an miR microarray.…”
Section: Introductionmentioning
confidence: 69%
“…In lung cancer, neuroendocrine features, which are associated with an aggressive clinical course, were linked with miR‐375, 15 indicating a relationship between histopathology and miR expression. In MM, the expression profile and prognostic and diagnostic significance of miR have been reported; however, the significance of miR was not concordant, most likely due to the variety of approaches, techniques and collected samples 16,17 . In this study, we identified high expression of miR‐199/214 in SM with an miR microarray.…”
Section: Introductionmentioning
confidence: 69%
“…The definite diagnosis of mesothelioma is often challenging and complex, and the qualitative analysis of markers in pleural tissue via immunohistochemical test is the gold standard. Therefore, miRNAs and their molecular mechanisms that are associated with mesothelioma development could be potential diagnostic markers in mesothelioma [144]. Guled et al conducted the first study aimed at assessing the expression of miRNAs in mesothelioma.…”
Section: Mir-144 In Mesotheliomamentioning
confidence: 99%
“…Whilst the only well‐founded current routinely available molecular technique for mesothelioma diagnosis is FISH for p16 deletion (and this is referred to briefly in the guideline), there are many other techniques that are evolving and which may become more widely available in the future. These include microRNA expression and DNA methylation in tissue or in circulating tumour cells/circulating tumour DNA . Any update of the guidelines will need to introduce these and discuss any potential role they may have now, or promise they might have for the future.…”
Section: Discussionmentioning
confidence: 99%